Host–parasite relationship in urban environments: A network analysis of haemoparasite infections in Nasua nasua Linnaeus (South American coati) - Santos, Filipe Martins; Sano, Nayara Yoshie; Perles, Livia [UNESP]; André, Marcos Rogério [UNESP] (Wiley, 2025)
Parasite relationships are influenced by host size, behaviour, population density and location and can affect the ecological dynamics of their hosts. Urban environments provide new contexts for host–parasite interactions, often leading to changes in infection dynamics when compared with the natural environment. This study focuses on the relationship between five genera of haemoparasites (Anaplasma Theiler, Ehrlichia Moshkovski, Hepatozoon Miller, haemotropic Mycoplasma Nowak and Neorickettsia Philip) found in the South American coati Nasua nasua Linnaeus (Carnivora: Procyonidae), a carnivore highly adaptable to urban areas. Here, we used network analysis to verify the interaction between N. nasua and haemoparasites. We also used a General Linear Model to investigate the influence of biotic and abiotic variables and haemoparasite infections on the functional roles of N. nasua individuals, considering weight, age, sex and tick infestation (number of immature ticks collected). The network revealed low modularity, and none of the biotic variables, immature stages of ticks and location of sampling had any influence on the functional role of N. nasua. The most important haemoparasite in the network was haemotropic Mycoplasma, identified as a key non-hub connector, probably spreading efficiently through frequent agonistic social interactions from N. nasua. These findings underscore the complex interplay between host behaviour, environmental factors and parasite ecology in urban environments, offering insights into managing urban wildlife diseases.
Keywords: coati; network metrics; social behaviour; urban forest fragments